Instrumentation of Microscale Techniques for Biochemistry Teaching at FES Zaragoza, UNAM - Araceli García-del Valle; María Teresa Corona-Ortega; Margarita Cruz-Millán; Antonia Guillermina Rojas-Fernández; Miguel Aguilar-Santelises; Leonor Aguila-Santelises (Multidisciplinary Journal for Education, Social and Technological Sciences)
Biochemistry teaching requires many laboratory sessions where theoretical knowledge may be put on test. At the same time, there is always some risk due to exposure to toxic materials, dangerous chemicals storage and waste disposal. Compliance with new regulations to prevent environmental contamination may also constitute a real hindrance for biochemistry teaching as experimental science. Therefore, we have designed microscale techniques, in order to reduce costs as well as the negative impact of laboratory practical sessions due to risk and environmental contamination. To develop microscale techniques does not only mean to reduce equipment size and amount of the reagents that are required for the usual experiments. Microscale techniques serve particularly well as a motivating approach to experimental biochemistry teaching that produces highly motivated students at the same time that requires minor costs, decreases working time, laboratory space, reagents volume and diminishes the generation of dangerous waste. We have demonstrated all these positive effects in biochemistry teaching and prompted the formal implementation of microscale techniques into the formal activities from the Cell and Tissue Biochemistry Laboratory I (BCT-I) from the Chemistry, Pharmacy and Biology (QFB) curricula at the National Autonomous University of Mexico (UNAM). First, we reviewed the BCT-I manual, choosing all the laboratory practices that might be microscaled. Then, we elaborated and validated all necessary protocols to analyse linearity, accuracy and reproducibility of the determinations, demonstrating that microscale techniques allow truthful results, comparable to full scale techniques.